1990
DOI: 10.1136/gut.31.10.1130
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and investigative findings in 145 patients with tuberculous peritonitis diagnosed by peritoneoscopy and biopsy over a five year period.

Abstract: (Table II).Haematological investigations (n= 145) showed a mean haemoglobin concentration of 11 g/dl (range 6-15 g/dl), a mean total white cell count of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
108
1
5

Year Published

1998
1998
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(124 citation statements)
references
References 10 publications
10
108
1
5
Order By: Relevance
“…We found that leucocytosis was more common than leucopenia (22% vs 15%) which was similar to that reported by Manohar et al 18 in the pre HIV era in Durban.…”
Section: Preoperative Investigationssupporting
confidence: 91%
See 4 more Smart Citations
“…We found that leucocytosis was more common than leucopenia (22% vs 15%) which was similar to that reported by Manohar et al 18 in the pre HIV era in Durban.…”
Section: Preoperative Investigationssupporting
confidence: 91%
“…78,81 Fever was less common in our series (24%) than in others (46% to 92%). 78,79,80 Ascites was present in 94-95% of patients in some of the series in the past 18,78 and in 61-65% of patients in some of the recent series, 56,83 …”
Section: Clinical Characteristicsmentioning
confidence: 96%
See 3 more Smart Citations